Review—Heteroatom-Doped High Porous Carbon Metal Free Nanomaterials for Energy Storage and Conversion. (1st September 2022) - Parkash, Anand; Solangi, Nizamuddin; Seehar, Tahir Hussain; Zhang, Ge; Akram, Muhammad; Ali, Salamat
Abstract : The fuel cell is one of the most environmentally friendly methods for sustainably converting chemical energy to electricity. The broad use of the oxygen reduction process (ORR) at the cathode has been hindered up until this point by the pricy platinum catalysts required. The amount of noble metal needed for the requisite catalytic effect may be reduced using nonprecious-metal catalysts. Still, they are either too expensive for the commercial mass production of clean energy or their energy conversion efficiency is too low. The cheap cost, broad surface area, high electrical conductivity, abundant electrocatalytic active sites, and corrosion-resistant features have led to a new class of carbon-based, metal-free catalysts. These catalysts might significantly reduce the price and increase the effectiveness of fuel cells when utilized as substitute ORR catalysts. This review article describes several metal-free carbon-based catalysts that have been developed employing very complex designs and rational heteroatom doping (by intrinsic and macroscopic tuning).